Do the dynamics of vaccine programs improve the full immunization of children under the age of five in Cameroon? - Rodrigue Nda'chi Deffo; Benjamin Fomba Kamga (BMC, 2020)
Abstract Background Among the eight Millennium Development Goals (MDGs), three were devoted to health. Two amongst which MDG4 in relation to the reduction of infant mortality has not been achieved in Least Developed Countries (LDC). In Africa, a significant part of infant mortality is due to vaccine-preventable diseases administered free of charge by the Extended Program on Immunization (EPI). As such, in the "social equity" pillar of Sustainable Development Goals (SDG), the MDGs related to health have yet been taken into account. The achievement of these objectives requires an understanding of the immunization behavior of children under 5 years of age through an analysis of immunization dynamics between 1991 and 2011. Methods We use data from Demographic and Health Surveys (DHS) of 1991, 1998, 2004 and 2011 carried out by the National Institute of Statistics (NIS). The module concerning EPI vaccines was administered to 3350, 2317, 8125 and 25,524 under 5 in 1991, 1998, 2004 and 2011 respectively. The Immunization analysis was made from the logistic model for complete immunization and the Oaxaca's decomposition to assess the contribution of the unexplained part, which is that of the strategies/programs implemented between 1991 and 2011 by the EPI to improve immunization. Results In general, children with vaccination card are more than 7 times likely to be fully immunized than their counterparts who do not have any. This result was higher in 1991 (approximately 57) and lowest in 2011 (5). In addition, the child's birth order reduces his/her probability of being fully immunized and the impact increases with the latter's birth order. On the other hand, the mother's age as well as her level of education increase the child's likelihood of receiving all basic vaccines. Moreover, the contributions of EPI partners in terms of immunization support as well as strategies to promote immunization through communication for development are of a particular importance in increasing immunization coverage. They significantly explain 67.62% of the 0.105 gain recorded within the 2011-2004 period and 72.46% of the 0.069 gain recorded within the 2004-1998 period. Conclusion The contribution of EPI partner organizations is fundamental for the achievement of EPI objectives. Since they contribute to increase the likelihood of fully immunized children. The link with child immunization is done through the specific characteristics to the mother.